Output, environmental pollution and health nexus in Vietnam: an estimation of simultaneous model with panel data. (2018) - Duong, Ha Hai; Jayanthakumaran, Kankesu
This paper estimates the provincial data of carbon dioxide emissions in 60 provinces in Vietnam for the years 2000 to 2010, and investigates the simultaneous relationships between output, environmental pollution and health in Vietnam. By applying the two-step system-dynamic GMM, lagged effects, endogeneity, heteroscedasticity, and autocorrelation for the variables have been addressed. The results show that increase in output causes an increase in the emissions. Meanwhile, an increase in emissions causes bad population health in the Mekong River Delta region, one of the highest tuberculosis incidence regions in Vietnam. The results also demonstrate that population health is an important input into economic growth in Vietnam. Better population health leads to increased output. Findings have policy implications for health, pollution and investment related issues for Vietnam.